2011
DOI: 10.1021/la200103w
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step Seeding Procedure for Preparing HKUST-1 Membrane on Porous α-Alumina Support

Abstract: Metal-organic framework (MOF) membranes have attracted considerable attention because of their striking advantages in small-molecule separation. The preparation of an integrated MOF membrane is still a major challenge. Depositing a uniform seed layer on a support for secondary growth is a main route to obtaining an integrated MOF membrane. A novel seeding method to prepare HKUST-1 (known as Cu(3)(btc)(2)) membranes on porous α-alumina supports is reported. The in situ production of the seed layer was realized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(144 citation statements)
references
References 24 publications
9
133
2
Order By: Relevance
“…For example, Shekhah et al have demonstrated the homogeneous, structurally well-defined HKUST-1 ([Cu 3 (btc) 2 ]) structures on a gold substrate, 299 and Nan et al have reported another LbL-based seeding method to prepare HKUST-1 on porous α-alumina supports. 300 In these cases, a bare substrate is first immersed into the linker solution. The linker-functionalized substrate is then further immersed in a metal precursor solution and subsequently in a solution of the organic ligand with a solvothermal treatment thus forming the first layer.…”
Section: Expansion Of Conceptmentioning
confidence: 99%
“…For example, Shekhah et al have demonstrated the homogeneous, structurally well-defined HKUST-1 ([Cu 3 (btc) 2 ]) structures on a gold substrate, 299 and Nan et al have reported another LbL-based seeding method to prepare HKUST-1 on porous α-alumina supports. 300 In these cases, a bare substrate is first immersed into the linker solution. The linker-functionalized substrate is then further immersed in a metal precursor solution and subsequently in a solution of the organic ligand with a solvothermal treatment thus forming the first layer.…”
Section: Expansion Of Conceptmentioning
confidence: 99%
“…[18] The growth of HKUST-1 onto a range of smooth surfaces such as polymeric, gold, ceramic, and quartz have been studied. [19] Using a step-by-step process, Nan et al [20] grew HKUST-1 onto porous α-aluminum discs, using 1:1 water:ethanol solvent system in a multistep process. In this work, HKUST-1 was grown on the surface of the three cross-linked electrospun membranes using ethanolic solutions.…”
Section: Growth Of Hkust-1mentioning
confidence: 99%
“…Recently, Nan et al [56] reported the synthesis of CuBTC on a-alumina support by a combination of suitable seeding with mother liquors. They performed seeding through immersion in a smooth support for each solution containing a metal salt and ligand.…”
Section: Solvothermal Synthesis: Direct and Secondary Growthmentioning
confidence: 99%